2008
DOI: 10.1093/ndt/gfn236
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria associated with indicators of inflammatory activity in an HIV-positive population

Abstract: Background. The survival of human immunodeficiency virus (HIV)-infected patients has increased significantly since the introduction of combination antiretroviral therapy, leading to the development of important long-term complications including cardiovascular disease (CVD) and renal disease. Microalbuminuria, an indicator of glomerular injury, is associated with an increased risk of progressive renal deterioration, CVD and mortality. However, the prevalence of microalbuminuria has barely been investigated in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
43
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 40 publications
8
43
1
Order By: Relevance
“…The prevalence of proteinuria among studies varied, ranging from 7 to 32% [19,20,21,22], while those of microalbuminuria and albuminuria were 9.4% (495 Caucasian HIV subjects in Norway) and 11% (Study of Fat Redistribution and Metabolic Change in HIV Infection (FRAM) cohort, representative of HIV patients in the USA), respectively [23,24]. In the USA, the reported prevalence of CKD in HIV-infected patients ranged between 15.5 and 23.7%, and of CKD ≥ stage 3 between 5.9 and 9.7% [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of proteinuria among studies varied, ranging from 7 to 32% [19,20,21,22], while those of microalbuminuria and albuminuria were 9.4% (495 Caucasian HIV subjects in Norway) and 11% (Study of Fat Redistribution and Metabolic Change in HIV Infection (FRAM) cohort, representative of HIV patients in the USA), respectively [23,24]. In the USA, the reported prevalence of CKD in HIV-infected patients ranged between 15.5 and 23.7%, and of CKD ≥ stage 3 between 5.9 and 9.7% [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…1 The reported prevalence of CKD in patients infected with HIV in North America and Europe ranges from 4.7% to 9.7%, and higher rates have been reported when CKD is defined by either estimated glomerular filtration rate (eGFR) or proteinuria. [2][3][4] HIV infection is a well-established risk factor for CKD and endstage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that HIV infection is associated with tubular or glomerular defects, therefore the urinary excretion of various proteins, including B2M, might be increased. [19][20][21] Surprisingly, the urinary levels of IP-10 and B2M were higher in healthy volunteers than in HIV-infected patients virally suppressed with TDF/FTC/EFV. Previous observational studies suggest that the urinary B2M level would be increased in patients receiving tenofovir-based regimens due to tenofovir-induced tubulopathy.…”
Section: Discussionmentioning
confidence: 94%